2010
DOI: 10.1074/jbc.m109.071084
|View full text |Cite
|
Sign up to set email alerts
|

Increased Receptor Stimulation Elicits Differential Calcium-sensing ReceptorT888 Dephosphorylation

Abstract: EXPERIMENTAL PROCEDURESMaterials-Fura-2/AM was from Molecular Probes, Inc. (Invitrogen). Horseradish peroxidase-conjugated anti-mouse and anti-rabbit secondary antibodies were from Dako (Ely, Cambridgeshire, UK). Unless stated otherwise, all other chemicals were purchased from Sigma-Aldrich (Poole, Dorset, UK).Cell Culture-HEK-293 cells, stably transfected with human parathyroid CaR (11), were a gift from Dr. E. F. Nemeth (NPS Pharmaceuticals). Cells were grown in Dulbecco's modified Eagle's medium supplemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…9,10 Indeed, mild acidosis (pH o 7.2) significantly inhibited Ca renders the CaR inactive), variations in pH o between 7.2 and 7.6 had no effect on actin polymerization. This finding indicates that changing pH o does not otherwise affect baseline signaling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 Indeed, mild acidosis (pH o 7.2) significantly inhibited Ca renders the CaR inactive), variations in pH o between 7.2 and 7.6 had no effect on actin polymerization. This finding indicates that changing pH o does not otherwise affect baseline signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Normal human parathyroid cells were obtained by collagenase-digestion after neck surgery 9 (procedures performed under institutional ethical guidelines and with patients' written informed consent). PTH levels 9 ), and 1 mg/ml BSA.…”
Section: Parathyroid Gland Preparation and Pth Secretion Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Such a mechanism could explain how the C-terminal truncation mutant R866X abolished Ca 2+ i mobilization. G 12 has also been reported to activate protein phosphatase 2A [29], an enzyme that supports Ca 2+ o -stimulated dephosphorylation of CaSR residue T888 and, in turn, promotes stable elevations in Ca 2+ i [30]. Preliminary experiments investigating the effects of pretreatment with pertussis toxin and of acute exposure to the broad-spectrum phosphodiesterase (PDE) inhibitor IBMX demonstrated that the suppressive effect of Ca 2+ o on forskolin-induced elevations in cAMP levels was dependent on G i/o -mediated inhibition of adenylyl cyclase and not PDE.…”
Section: Discussionmentioning
confidence: 99%
“…2; wt, 3.0G0.1 mM; T888M, 2.5G0.2 mM; P!0.05 by unpaired t-test of log EC 50 values). Western blotting revealed similar expression of protein bands consistent with the wellrecognized 140 kDa core-glycosylated and 160 kDa mature receptors (7,(12)(13)(14)(15)20) in both sets of transfected cells (Fig. 2C).…”
Section: T888m Mutation In Hek-293 Cellsmentioning
confidence: 71%